SISTEM INFORMASI MONEV (MONITORING DAN EVALUASI) KEUANGAN PADA PT. SUMBER REZEKI JATIADI GENDING - Ja'far Shudiq, Wali (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
PT. Sumber Rezeki is one of the relatively large places for depositing junk goods in the Jatiadi area. In the system for calculating the results of the scales, sales and purchases are still recorded in the book. This often causes problems, where data is lost due to damaged records/books, so transaction data cannot be found. Employee payroll is still conventional, there is no fact of reporting payroll so that the financial reports are not recorded. Without payroll reporting, business owners do not know the salaries given to employees per month as well as expenses from suppliers that add up and there are still errors in calculating the total transaction. Therefore, an Information System Application for Monev (Monitoring and Evaluation) of Junk Goods Business Finance at PT. Sumber Rezeki Jatiadi Gending with the aim of making it easier for junk business owners to make transactions, payroll according to attendance, monitor and evaluate business finances, and find out the results of recapitulation of financial report data every month, so that PT. Sumber Rezeki is able to compete with other scrap businesses. For the method used, namely the waterfall, the process is carried out sequentially or sequentially linear, for system design using Flowchart, DFD, and ERD.